2017
DOI: 10.1093/nc/niw022
|View full text |Cite
|
Sign up to set email alerts
|

Global and local complexity of intracranial EEG decreases during NREM sleep

Abstract: Key to understanding the neuronal basis of consciousness is the characterization of the neural signatures of changes in level of consciousness during sleep. Here we analysed three measures of dynamical complexity on spontaneous depth electrode recordings from 10 epilepsy patients during wakeful rest (WR) and different stages of sleep: (i) Lempel–Ziv complexity, which is derived from how compressible the data are; (ii) amplitude coalition entropy, which measures the variability over time of the set of channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
177
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 123 publications
(209 citation statements)
references
References 44 publications
31
177
1
Order By: Relevance
“…The amount of irregularity in time series patterns reflects linear stochastic effects as well as nonlinear deterministic correlations (Courtiol et al, 2016;Kaffashi, Foglyano, Wilson, & Lopario, 2008;Park, Kim, Kim, & Cichocki, 2007;Wang, McIntosh, Kovacevic, Karachalios, & Protzner, 2016). Surrogate data analyses, which involve preserving the linear properties of neural time series while simultaneously altering the underlying temporal dependencies via phase randomization, provide a more explicit test for the presence of nonlinearities (Theiler, Eubank, Longtin, Galdrikian, & Farmer, 1992), yet they have not been used frequently (for an exception, see Schartner, Pigorini, et al, 2017). The authors concluded that high frequency spectral components were entropy raising and lower frequencies entropy suppressing (see also Lee et al, 2013;Mizuno et al, 2010), and that overall, entropy reflects the balance between sleep and alertness promoting factors.…”
Section: Changes In Eeg Multiscale Entropy and Power-law Frequency mentioning
confidence: 99%
See 4 more Smart Citations
“…The amount of irregularity in time series patterns reflects linear stochastic effects as well as nonlinear deterministic correlations (Courtiol et al, 2016;Kaffashi, Foglyano, Wilson, & Lopario, 2008;Park, Kim, Kim, & Cichocki, 2007;Wang, McIntosh, Kovacevic, Karachalios, & Protzner, 2016). Surrogate data analyses, which involve preserving the linear properties of neural time series while simultaneously altering the underlying temporal dependencies via phase randomization, provide a more explicit test for the presence of nonlinearities (Theiler, Eubank, Longtin, Galdrikian, & Farmer, 1992), yet they have not been used frequently (for an exception, see Schartner, Pigorini, et al, 2017). The authors concluded that high frequency spectral components were entropy raising and lower frequencies entropy suppressing (see also Lee et al, 2013;Mizuno et al, 2010), and that overall, entropy reflects the balance between sleep and alertness promoting factors.…”
Section: Changes In Eeg Multiscale Entropy and Power-law Frequency mentioning
confidence: 99%
“…The rationale for use of the surrogates is the following: linear processes are completely accounted for by the second order statistics (power spectrum) of a time series. Surrogate sets were generated separately for every participant, electrode channel and sleep stage (using a maximum number of 100 iterations) and then, these surrogates were used to construct ratio scores of original relative to surrogate data, similar to what has been reported in other studies (Schartner, Carhart-Harris, et al, 2017;Schartner, Pigorini, et al, 2017). The surrogate signals are generated by keeping the power spectrum constant, while randomly shuffling phase (which destroys higher-order correlations) and in the final step, performing an inverse Fourier transform back into the time domain (Theiler et al, 1992).…”
Section: Surrogate Controlsmentioning
confidence: 99%
See 3 more Smart Citations